Neural reward related-reactions to monetar gains for self and charity are associated with donating behavior in adolescence - Spaans, Jochem P (Soc Cogn Affect Neurosci, 2020)
The aim of the current study was to examine neural signatures of gaining money for self and charity in adolescence. Participants (N = 160, aged 11–21) underwent functional magnetic resonance imaging-scanning while performing a zero-sum vicarious reward task in which they could either earn money for themselves at the expense of charity, for a self-chosen charity at the expense of themselves, or for both parties. Afterwards, they could donate money to charity, which we used as a behavioral index of giving. Gaining for self and for both parties resulted in activity in the ventral striatum (specifically in the NAcc), but not gaining for charity. Interestingly, striatal activity when gaining for charity was positively related to individual differences in donation behavior and perspective taking. Dorsal anterior cingulate cortex, insula and precentral gyrus were active when gaining only for self, and temporal-parietal junction when gaining only for charity, relative to gaining for both parties (i.e. under equity deviation). Taken together, these findings show that striatal activity during vicarious gaining for charity depends on levels of perspective taking and predicts future acts of giving to charity. These findings provide insight in the individual differences in the subjective value of prosocial outcomes.